Analytic network process: An overview of applications - Kheybari, Siamak; Rezaie, Fariba Mahdi; Farazmand, Hadis (Applied mathematics and computation, 2020)
•We conduct a state-of the-art literature review on analytical network process.•The database for the review contains 456 papers.•This review categorizes 456 scholarly papers into nine application areas.•This paper provides useful insights into the anatomy of analytical network process. The analytic network process is one of the multi-criteria decision-making methods widely used to solve various issues in the real-world due to the consideration of complex and interrelated relationships between decision elements and the ability to apply quantitative and qualitative attributes simultaneously. The purpose of this paper is to review and categorize ANP studies previously conducted. For this purpose, 456 valid scientific papers are reviewed from 2000 to 2017 (in May 2017). The articles are classified in nine application areas: (1) health, safety and environmental management; (2) hydrology and water management; (3) business and financial management; (4) human resources management; (5) tourism; (6) logistics and supply chain management; (7) design, engineering and manufacturing systems; (8) energy management and (9) other topics. After reviewing the papers in the nine application areas, some suggestions for future research are presented. This article provides useful information on ANP for scholarly researchers.